Child Marriage: Motives and Intergenerational Phenomenon - Azinar, Muhammad; Shaluhiyah, Zahroh; Jati, Sutopo Patria; Purnami, Cahya Tri (Jurnal Kesehatan Masyarakat, 2024)
The Law on Marriage has been amended, but the prevalence of child marriage has not been reduced significantly. Grobogan is one of the areas with the highest prevalence of married and pregnant women at child age (less than 19 years) in Central Java, and is always above the national prevalence. During 2018 the prevalence of cases reached 59.88%, in 2019 it was 51.24%, in 2020 it was 52.81%, in 2021 it was 54.33%, and in 2022 it was 52.15%. Marriage of women at child age becomessocial phenomena that often occur in society.This research is an analytical survey with a cross-sectional design. The research uses a purposive sampling technique, namelyof all women who married at the age of less than 19 years in Grobogan district in the last 5 years (2018-2022), namely 2,676 cases. Data were analyzed to describe trends in cases and motives for marriage between women as children, as well as bivariate analysis using the Chi-square test to analyze the relationship between parents' marital history and children's marriages.The results of the research are that cases of child marriage (less than 19 years old) are more common among girls. Women are the ones who mostly marry under the age of 19. The most common cause (76.8%) underlying applications for marriage dispensation is dating behavior. Based on the pattern of child marriage couples that occurred in the last 5 years in Grobogan district, the most frequent marriages were women aged children (less than 19 years) marrying men aged adults (more than 19 years), namely 82.5%, there were 15.5 % of marriages that occurred between women and men who were both under 19 years of age, there were 1.8% of marriages that occurred between adult women (over 19 years) and men under 19 years of age, and 3 couples (0 .1%) married when both were 19 years old. There is a significant relationship between mothers' marital history and child marriages that occur in their daughters (p value 0.0002). This means that mothers who marry at a young age (less than 19 years) influence the occurrence of child marriage in their daughters.